An Analysis of Psychological Aspect of The Main Character in Shadow and Bone Movie - Priyanti, Maya Dwiayu; Tustiawati, Ida Ayu Mela (Austronesian: Journal of Language Science & Literature, 2025)
This study investigates the psychological dimensions of the main character in the film Shadow and Bone using Bernhardt’s (1953) theory of human motivation. The analysis focuses on five key motivational categories: organic needs, desire, emotions as motives, feelings and attitudes as motives, and social motives. Through qualitative descriptive methods, 24 instances of psychological motivation were identified from the film. The findings indicate that desire-related motivations (33.3%) and organic needs (29.1%) are most dominant in shaping the character of Alina, the protagonist. These motivations are closely tied to Alina’s experiences of personal conflict, social rejection, and emotional struggle, which drive her actions and development throughout the narrative. The study highlights how cinematic characters can serve as complex psychological representations, enriching narrative depth and enhancing audience empathy. This research contributes to the interdisciplinary discourse between psychology, literature, and film studies, emphasizing the importance of psychological realism in character construction.